Survey of Neonatal Intensive Care Unit Nurses' Use of a Motion/Sound Infant Seat. (April 2019) - Holmes, Margaret; Wright, Mary Ellen
Abstract : Background: Perinatal substance exposure is an increasing concern in infants being cared for in neonatal intensive care units. Current recommendations support nonpharmacologic treatments for this population of infants. Multimodal (motion, sound) seats are often employed to soothe infants. Purpose: The purpose of this study was to survey neonatal intensive care unit nurses on their practices regarding the use of a motion/sound infant seat. Methods: Sixty-six nurses (52% of 126 total nurses) completed the survey about their self-disclosed practices that included (1) reasons for use; (2) rationale for choice of settings of motion and sound; (3) duration of time infants spent in seat in one session; (4) perception of positive infant response; (5) who places infants in the seat; and (6) nursing instructions dispensed prior to use. Results: Chief reasons for use were infant state, lack of persons to hold infants, and a diagnosis of neonatal abstinence syndrome. Rationale for choice of motion and sound settings included trial and error, prior settings, personal preferences/patterns, assumptions, and random selection. Nurse responses regarding the amount of time the infant was placed in the seat in a single session ranged from 10 to 360 minutes, with determining factors of infant cues, sleeping, feeding, and someone else to hold the infant. Implications for Practice: As nonpharmacologic treatments evolve, nurses need guidelines for safe, effective interventions to care for infants. Implications for Research: Further research is necessary to ascertain the responses of withdrawing infants and to establish guidelines and education for use of the motion/sound infant seat.